Kajian Yuridis Pendirian Perseroan Terbatas Pasca Berlakunya Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Jodi Ghozali; Nizia Kusuma Wardani (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2023)
This research aims are to know the establishment of limited company after the effectivity of Law Number 11 of 2020 on Job Creation, and the existence of limited company organ in conducting legal matters. Type of this research was normative legal research which applied two types of approach, are statute and conceptual approaches. Based on this study, it can be known that the new concept of limited company after the implementation of job creation law is the capital association limited company and individual limited company which can be established by one person with establishment statement. Organ system within limited capital association company embrace two-tier board system, i.e organ which applied supervision system within the organ itself, thus it has general meeting of shareholder, board of direction and board of commissioner. In contrary, the individual limited company only applies one-tier board system i.e organ concept without using supervision body